Covid-19 in Asia : law and policy contexts - Ramraj, Victor Vridar, 1968- (New York, NY : Oxford University Press, 2021)
This is an edited collection of original essays on Asia's legal and policy responses to the COVID-19 pandemic, which, in a matter of months, swept around the globe, infecting millions. These jurisdiction-specific case studies and cross-cutting thematic essays cover five topics: first wave containment measures; emergency powers; technology, science, and expertise; politics, religion, and governance; and economy, climate, and sustainability.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 6, 2021).
Keywords: Public health laws -- Asia; COVID-19 (Disease) -- Law and legislation -- Asia; Communicable diseases -- Asia; COVID-19 (Disease) -- Social aspects -- Asia; Medical policy -- Asia; Law; Laws of specific jurisdictions & specific areas of law